2001
DOI: 10.1002/1097-4652(2001)9999:9999<1::aid-jcp1049>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-mediated proteolysis of vertebrate G1- and S-phase regulators

Abstract: Cell-cycle progression in all eukaryotes is driven by cyclin-dependent kinases (CDKs) and their cyclin partners. In vertebrates, the proper and timely duplication of the genome during S-phase relies on the coordinated activities of positive regulators such as CDK±cyclins and E2F, and negative regulators such as CDK inhibitors of the Cip/Kip and INK4 families. Recent and ongoing work indicates that many important regulators of G1-and S-phases are targeted for ubiquitination and subsequent degradation by the 26S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 137 publications
(279 reference statements)
2
57
0
Order By: Relevance
“…In the majority of examined cases, site-specific phosphorylation is required for targeting proteins for proteasomal degradation (Yew, 2001). Our initial observation of a strong correlation between forskolin-induced phosphorylation of cyclin D3 and its instability is in agreement with these findings, and supports the hypothesis that phosphorylation does have an important role in regulation of cyclin D3 stability.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the majority of examined cases, site-specific phosphorylation is required for targeting proteins for proteasomal degradation (Yew, 2001). Our initial observation of a strong correlation between forskolin-induced phosphorylation of cyclin D3 and its instability is in agreement with these findings, and supports the hypothesis that phosphorylation does have an important role in regulation of cyclin D3 stability.…”
Section: Discussionsupporting
confidence: 88%
“…Forskolin promotes cyclin D3 degradation via a proteasome-dependent pathway Many cell-cycle proteins, such as cyclins D1, E and A, are degraded by proteasome-mediated proteolysis (Yew, 2001). Therefore, we wished to determine the involvement of proteasome function in degradation of cyclin D3, and whether proteasomal activity is required for forskolin-mediated increase in cyclin D3 turnover.…”
Section: Forskolin Accelerates Cyclin D3 Turnovermentioning
confidence: 99%
“…UBC encodes a poly-ubiquitin precursor that can conjugate with different residues and lead to various effects within a cell (41). Yew (42) demonstrated that G1-and S-phase events in vertebrates, which were essential for cell proliferation, were specifically mediated by a multitude of regulators associated with ubiquitination, of which UBC was required. Furthermore, Gruber et al (43) reported that cells in IDD lost their ability to proliferate and were subject to senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were lysed and His-Ubiquitin was isolated using Ni-NTA beads as described in Materials and methods. The presence of HA-CK2b in these isolates was examined by Western blots using anti-HA antibodies Whereas the degradation of mitotic cyclins requires a destruction box, the degradation of G1 cyclins such as cyclin D and cyclin E involves regulatory phosphorylation events (Yew, 2001;Koepp et al, 2001). Phosphorylation of cyclin D by glycogen synthase kinase-3b is involved in triggering degradation of that cyclin while cell cycle dependent autophosphorylation of cyclin E is involved in its degradation (Diehl et al, 1998;Winston et al, 1999).…”
Section: Examination Of the Putative Destruction Box In Ck2bmentioning
confidence: 99%